Chiral bosons through linear constraints - Girotti, Horacio Oscar (1992)
We study in detail the quantization of a model which apparently describes chiral bosons. The model is based on the idea that the chiral condition could be implemented through a linear constraint. We show that the space of states is of an indefinite metric. We cure this disease by introducing ghost fields in such a way that a Becchi-Rouet-Stora-Tyutin symmetry is generated. A quartet algebra is seen to emerge. The quartet mechanism, then, forces all physical states, except the vacuum, to have a zero norm.